Uporaba zdravilnih rastlin pri zdravljenju živali - Munda, Miha (Farmacevtski vestnik, 2017)
The use of medicinal plants for the prevention and treatment of diseases is increasingly extended. By the observation of wild animals, the prehistoric human learned about the use of medicinal herbs for himself and for animals in captivity. In the past, medicinal herbs were very important for the development of synthetic drugs and were also the starting point for quicker development of modern medicine. Today, different medicinal plants can be used for animal treatment. Althought many people believe that medicinal plants are safe for use, more research about safety and possible interactions with others substances are necessary.
Keywords: animals; bolezni; disease; diseases; efficiency; medicinal plants; safety; security; učinkovitost; varnost; zdravilne rastline; živali